2007
DOI: 10.1007/s10658-007-9150-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of pathogenesis-related metabolites and their plausible pathways of induction in potato leaves following inoculation with Phytophthora infestans

Abstract: Metabolite profiles based on GC/MS were used to study the temporal dynamics of metabolites in potato leaves following pathogen inoculation. In the polar and non-polar plant extracts a total of 106 consistent peaks were detected, of which 95 metabolites were tentatively identified. Following pathogen inoculation, the abundances of 42 metabolites were significantly increased or decreased, and these metabolites were designated as Pathogenesis-Related (PR) Metabolites. Factor analysis of the abundance of 106 metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
4
31
1
Order By: Relevance
“…For example the increased exudation of secondary metabolites and amino acids through plant development might be indicative of innate defensive priming by the plant. Studies analyzing the metabolite profiles of potatoes after pathogen inoculation showed that 42 metabolites (consisting of sugars, amino acids, organic acids and fatty acids) significantly increased or decreased [64]. Similar to our exudation profiling over a developmental time course, metabolite profiling by Abu-Nada et al [64] revealed that pathogen inoculation lead to an up-regulation of amino acids and a down-regulation of sugars.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example the increased exudation of secondary metabolites and amino acids through plant development might be indicative of innate defensive priming by the plant. Studies analyzing the metabolite profiles of potatoes after pathogen inoculation showed that 42 metabolites (consisting of sugars, amino acids, organic acids and fatty acids) significantly increased or decreased [64]. Similar to our exudation profiling over a developmental time course, metabolite profiling by Abu-Nada et al [64] revealed that pathogen inoculation lead to an up-regulation of amino acids and a down-regulation of sugars.…”
Section: Discussionsupporting
confidence: 84%
“…Studies analyzing the metabolite profiles of potatoes after pathogen inoculation showed that 42 metabolites (consisting of sugars, amino acids, organic acids and fatty acids) significantly increased or decreased [64]. Similar to our exudation profiling over a developmental time course, metabolite profiling by Abu-Nada et al [64] revealed that pathogen inoculation lead to an up-regulation of amino acids and a down-regulation of sugars. Although our exudation profiles were obtained axenically, we observed the release of compounds that are released as defensive and priming strategies against pathogens or as attractors for beneficial microbes.…”
Section: Discussionsupporting
confidence: 84%
“…7. Similar results have been reported for other plants since Abu-Nada et al [41] found a much higher proportion of compounds being upregulated than those down-regulated in potato infected with Phytophtera infestans. In this study, we provide evidence that HLB induces production of hesperidin, quercetin, and naringenin.…”
Section: Compound Identification and Statistical Analysissupporting
confidence: 87%
“…The number of metabolites identified and the level of coverage are relatively low in comparison to Abu-Nada et al [43] who identified 95 polar metabolites including amino acids, fatty acids, organic acids and sugars in potato leaves following pathogen P. infestans inoculation. Similarly, a total of 180 polar and non-polar metabolites were identified in potato tubers by Shepherd et al [44].…”
Section: Metabolites Identifiedmentioning
confidence: 76%